Loss of the ciliary protein Chibby1 in mice leads to exocrine pancreatic degeneration and pancreatitis - Benjamin Cyge (Nature Portfolio, 2021)
Abstract Primary cilia protrude from the apical surface of many cell types and act as a sensory organelle that regulates diverse biological processes ranging from chemo- and mechanosensation to signaling. Ciliary dysfunction is associated with a wide array of genetic disorders, known as ciliopathies. Polycystic lesions are commonly found in the kidney, liver, and pancreas of ciliopathy patients and mouse models. However, the pathogenesis of the pancreatic phenotype remains poorly understood. Chibby1 (Cby1), a small conserved coiled-coil protein, localizes to the ciliary base and plays a crucial role in ciliogenesis. Here, we report that Cby1-knockout (KO) mice develop severe exocrine pancreatic atrophy with dilated ducts during early postnatal development. A significant reduction in the number and length of cilia was observed in Cby1-KO pancreta. In the adult Cby1-KO pancreas, inflammatory cell infiltration and fibrosis were noticeable. Intriguingly, Cby1-KO acinar cells showed an accumulation of zymogen granules (ZGs) with altered polarity. Moreover, isolated acini from Cby1-KO pancreas exhibited defective ZG secretion in vitro. Collectively, our results suggest that, upon loss of Cby1, concomitant with ciliary defects, acinar cells accumulate ZGs due to defective exocytosis, leading to cell death and progressive exocrine pancreatic degeneration after birth.